Interactions Between Teachers and Students with Disabilities in Inclusive Public Primary Schools in Togo - Rita Kadanga; TCHABLE Boussanlègue (International Journal of Educational Review, 2023)
This research examines the interactions between teachers and children with disabilities (CWD) in Togo's public elementary schools. The field survey involved 20 schools through 27 inclusive classrooms observations and over a hundred interviews with teachers as well as children with disabilities (CWD) and some of their parents. The findings show that relations between teachers and CWD pupils are positive, given that the teachers are aware of the challenges of inclusive education, but they complain about the lack of training in differentiated pedagogy, which prevents them from playing their roles effectively in inclusive classes.